Defining the true impact of coronavirus disease 2019 in the at-risk population of patients with cancer. (September 2020) - Angelis, Vasileios; Tippu, Zayd; Joshi, Kroopa; Reis, Sara; Gronthoud, Firza; Fribbens, Charlotte; Okines, Alicia; Stanway, Susannah; Cottier, Emma; McGrath, Sophie; Watkins, David; Noble, Jillian; et al.
Abstract: Background: In light of the coronavirus disease 2019 (COVID-19) pandemic, cancer centres in the United Kingdom and Europe re-organised their services at an unprecedented pace, and many patients with cancer have had their treatments severely disrupted. Patients with cancer were considered at high risk on sparse evidence, and despite a small number of emerging observational studies, the true incidence and impact of COVID-19 in the 'at-risk' population of patients with cancer is yet to be defined. Methods: Epidemiological and clinical data were collected prospectively for patients attending the Royal Marsden Hospital and three network hospitals between March 1st and April 30th 2020 that were confirmed to have Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection. Significance of clinical and pathological characteristics was assessed using the Fisher's exact test and Wilcoxon rank sum test, whilst univariate and multivariate logistic regression models were used to further assess risk. The number of patients attending in March/April 2020 for face-to-face attendances was also extracted. Findings: During the 2-month study period, 867 of 13, 489 (6.4%) patients met the criteria leading to swab testing. Of the total at-risk population, only 113 of 13, 489 (0.84%) were swab positive, 101 of 13, 489 (0.75%) required hospital admission and 29 of 13, 489 (0.21%) died of COVID-19. Of the patients that attended the hospital to receive cytotoxic chemotherapy alone or in combination with other therapy, 59 of 2001 (2.9%) were admitted to the hospital for COVID-19–related issues and 20 of 2001 (1%) died. Of the patients that collected targeted treatments, 16 of 1126 (1.4%) were admitted and 1 of 1126 (0.1%) died. Of the 11 patients that had received radiotherapy, 6 of 1042 (0.6%) required inpatient admission and 2 of 1042 (0.2%) died. Interpretations: Administration of systemic anticancer therapy appears to be associated with a modest risk of severe COVID-19 infection. Based on this snapshot taken as the first wave of COVID-19 hit our practice, we conclude that continuation of active cancer treatment, even in the palliative setting, is appropriate. Highlights: Of 13, 489 cancer patients, 867 were tested and 113 were coronavirus disease 2019 (COVID-19) swab-positive. Of these only 101 patients required hospital admission and 29 died of COVID-19. Systemic anticancer therapy (SACT) and radiotherapy confer only a modest risk of significant COVID-19 infection. Incidence of clinically significant COVID-19 was as in the general population. We encourage oncology centres to continue to deliver SACT and radiotherapy.